Studi Kefektifan Dinding Geser pada Bangunan Tingkat Tinggi Dalam Mengurangi Simpangan Struktur - Evantianus Sansujaya; Jusuf J.S. Pah; I Made Udiana (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2021)
The main principle of designing the multi-storey building is increasing the building strength on lateral force. The higher the building, then the more vulnerable the building in resisting the lateral force, such as earthquake force. In structure design in multi-storey building, there are 2 systems lateral force restraint that often used, that are frame that use shear wall and frame without shear wall. The purpose of this research is to analyze the effect of shear wall placement with respect to structure deflection as an effect of quake load also to find out the sensitivity of the adding the amount of shear wall on decreasing rate of structure deflection as an effect of quake load, that the calculation of quake load effect done by use the Equivalent Static Analysis Method. The result of the analysis obtained the structure deflection decreases with the increasing of the amount of shear wall and the average of decreasing rate of structure deflection for every addition of 1% shear wall is 1.97% also the layout of shear wall placement very react on structure deflection alteration.